THE ROLE OF ENTREPRENEURSHIP EDUCATION IN A DISRUPTIVE AGE - Achmad Yanu Alif Fianto; Siti Asiyah; Baiq Handayani Rinuastuti (Master of Management, Mataram University, 2020)
This study aims to determine (1) the influence of entrepreneurship education on entrepreneurship motivation ofmanagement student and (2) the influence of entrepreneurship education on entrepreneurial skills of management education student. This research is associative causal research with a quantitative approach. The variables of this research are in entrepreneurship education as independent variables, motivation and entrepreneurial skills as the dependent variable. The sample of population in this research is management education student respondents for about 213 students in East Java, Indonesia. Data collection techniques in this research using questionnaires and documentation. Data analysis method used was Structural Equation Model-Partial Least Square. This research finds that entrepreneurship education have a positive and significant effect towards entrepreneurship motivation and this research also finds that entrepreneurship education have a positive and significant effect towards entrepreneurship skill. From those findings, this research concludes that entrepreneurship education have a significant role in the disruptive age.